The comparison of efficiency between conventional sickle and inertial sickle: case study at Felcra Bukit Sedanan Berhad / Muhammad Fadhli Ahmad - Ahmad, Muhammad Fadhli (Faculty of Plantation and Agrotechnology, 2018)
Oil palm tree also known as Elaeis guineensis was originated from the West Africa. In Malaysia, Malaysian’s agriculture sector helping grower and processor to ease inflation by growing GDP of oil palm sector. After that, it also want to increase the performance in downstream industries such as food and edible oil processing (Kuncinas, P., 2017). In oil palm harvesting process, chisel and sickle is the main equipment. Nowadays, there are so many improvement of sickles has been done to make harvesting process easier. One of innovation has been done by UiTM which is inertial sickle. To prove inertial sickle is efficient than conventional sickle, this study was done to know about the efficiency for inertial sickle and to compare the efficiency using conventional sickle and inertial sickle. The data collection methods used in this study are face to face interview and experimental data. Experimental data was taken by using Polar RS800CX to get data of time, energy (K cal), average of heart rate (bpm) and numbers of heartbeat (beats) for workers at Felcra. The samples of worker is 13 persons total number of workers. The oil palm trees used in this study are having the average age of 10 years old. As the results were analyzed, it showed that there is a significant difference in the performance of inertial sickle and conventional sickle in term of time, average of heart rate and numbers of heartbeat because mean of inertial sickle was lesser compared conventional sickle. It showed that the performance of inertial sickle is better compared to conventional sickle. From the study, it can be conclude that the inertial sickle is far better in terms of performance but it is recommended that there are some improvements on the sickle need to be done especially in the blade aspects and spring cover.